2017
DOI: 10.3389/fncel.2017.00348
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Changes in the Vestibular System of Land Snail to a 30-Day Spaceflight and Readaptation on Return to Earth

Abstract: The vestibular system receives a permanent influence from gravity and reflexively controls equilibrium. If we assume gravity has remained constant during the species' evolution, will its sensory system adapt to abrupt loss of that force? We address this question in the land snail Helix lucorum exposed to 30 days of near weightlessness aboard the Bion-M1 satellite, and studied geotactic behavior of postflight snails, differential gene expressions in statocyst transcriptome, and electrophysiological responses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Time course of return to normal sensitivity in toadfish afferents paralleled the reported decrease in vestibular disorientation in astronauts after return from shuttle missions ( Reschke et al, 1994 ). Although belonging to a distinct group of animals, recordings taken directly from gravitoreceptors of the land snail (phylum Mollusca), and thus no intervening synapse as in afferent recordings, after exposures of 12–16 ( Balaban et al, 2011 ) and 30 ( Aseyev et al, 2017 ) days in space also showed a pronounced response hypersensitivity to tilt. In a complimentary study in tilapia the gain of an otolith-related vestibuloocular reflex was significantly increased within the first postflight week, and returned to control levels in the second postflight week, of space missions ( Sebastian et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…Time course of return to normal sensitivity in toadfish afferents paralleled the reported decrease in vestibular disorientation in astronauts after return from shuttle missions ( Reschke et al, 1994 ). Although belonging to a distinct group of animals, recordings taken directly from gravitoreceptors of the land snail (phylum Mollusca), and thus no intervening synapse as in afferent recordings, after exposures of 12–16 ( Balaban et al, 2011 ) and 30 ( Aseyev et al, 2017 ) days in space also showed a pronounced response hypersensitivity to tilt. In a complimentary study in tilapia the gain of an otolith-related vestibuloocular reflex was significantly increased within the first postflight week, and returned to control levels in the second postflight week, of space missions ( Sebastian et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…The standard vivarium cages used for housing rodents on Earth are not suitable for spaceflight experiments 22,23 . Therefore, over the years mice and rats have been flown and housed in various cages including the Japanese Aerospace Exploration Agency (JAXA) Habitat Cage 24 , animal carrying space capsules used on the BION-M1 unmanned Russian satellite 25,26,27 , the Mice Drawer System (MDS) designed by the Italian Space Agency 28,29,30 , the NASA Animal Enclosure Module (AEM), and now the NASA Rodent Transporter and Habitats…”
Section: Introductionmentioning
confidence: 99%